The effects of IL-1A and IL-6 genes polymorphisms on gene expressions, hormonal and biochemical parameters in polycystic ovary syndrome. (3rd April 2017) - Eser, Betul; Islimye Taskin, Mine; Hismiogullari, Adnan Adil; Aksit, Hasan; Bodur, Abdurrahman Said
Abstract: Polycystic ovary syndrome (PCOS) is a multifactorial disease characterised by chronic inflammation. We aimed to investigate an association between IL-1A and IL-6 gene polymorphisms and both hormonal/biochemical parameters and levels of IL-1A and IL-6. A total of 103 women diagnosed with PCOS according to ESHRE/ASRM criteria were investigated. The patients were divided into two groups as obese and non-obese. IL-1A and IL-6 genes polymorphisms as well as hormonal/biochemical parameters and levels of IL-1A and IL-6 were analysed in the same groups. Serum IL-1A and IL-6 levels were found to increase both in obese and non-obese groups. However, there was no association between IL-1A level and IL-1A polymorphism. A relationship was detected between H score, FSH, LH, total testosterone, HDL-C and TG levels and CG + GG genotypes of IL-6. Furthermore, an association was found between IL-6 levels and CC genotype of IL-6 in the obese PCOS patients. The abnormalities in hormonal/biochemical parameters detected in Turkish PCOS patients may be related with IL-6 gene polymorphism rather than IL-1A.